The impact of share price on open market share repurchases in Malaysia - Goh, Shin Peih (Universiti Malaysia Sarawak (UNIMAS), 2012)
The purpose of this study is to examine the price behavior of the firms following open market share repurchases in Malaysia. Specifically, this study attempt to test on the impact of share prices of public listed firms listed in Bursa Malaysia on the day of the repurchases and the long run performance after share repurchases took place. This study uses the daily data of the firms' share price collected from the Thomson Reuters Datastream database and the date of actual share repurchases from Bursa Malaysia. The results show that the price impact on the share repurchases day exhibit a positive abnormal return of 0.56% throughout the four years period of study. The long run performance shows the buy-and-hold abnormal return of 46.62% throughout the study. The results indicate that the signaling hypothesis and undervaluation hypothesis exist as investors react positively on firms repurchasing their shares and perceived the firms to be undervalued. The findings of this study are consistent with the findings found in prior studies.